The Implications of Titanium Alloys Applied in Maxillofacial Osteosynthesis - Mircea Riviș; Ciprian Roi; Alexandra Roi; Diana Nica; Adina Văleanu; Laura-Cristina Rusu (Applied Sciences, 2020)
Titanium alloys are known for their biological, mechanical and chemical properties, which have successfully expanded their use in the maxillofacial field. The internal fixation using titanium miniplates and screws offer a new perspective for the treatment of trauma and in orthognathic surgery and maxillofacial oncology. Although, titanium is highly recommended for its excellent biocompatibility, recent research has focused on identifying the potential local and general implications of the interactions between the human tissue and the metallic particles. This present review aims to outline the existing tissue changes, cellular alterations and future perspectives regarding the use of titanium-based alloys as osteosynthesis materials, taking into consideration the existing present debate whether the routinely removal of these materials should be an indication.